Respostas

2014-08-07T22:17:43-03:00
Olá, Agnesramos!

(x+3)(x+2) + 3(x+3)
x² + 2x + 3x + 6 + 3x + 9 = 0
x² + 2x + 3x + 3x + 6 + 9 = 0
x² + 8x + 15 = 0
a = 1
b = 8
c = 15

Δ = b² - 4ac
Δ = 8² - 4.1.15
Δ = 64 - 60
Δ = 4

-b +- √Δ / 2.a
-8 +- √4 / 2.1
-8 +- 2 / 2

x' = -8+2/2 = -6/2 = -3
x'' = -8-2/2 = -10/2 = -5

S = {-3, -5}

(x+1)(x+2) - 2(x-3) = 10
x² + 2x + x + 2 - 2x + 6 = 10
x² + 2x + x + 2 - 2x + 6 - 10 = 0
x² + 2x - 2x + x + 2 + 6 - 10 = 0
x² + x + 8 - 10 = 0
x² + x - 2 = 0
a = 1
b = 1
c = -2

Δ = b² - 4ac
Δ = 1² - 4.1.(-2)
Δ = 1 + 8
Δ = 9

-b +- √Δ / 2.a
-1 +- √9 / 2.1
-1 +- 3 / 2

x' = -1+3/2 = 2/2 = 1
x'' = -1-3/2 = -4/2 = -2

S = {1, -2}